PENGARUH PEMBERIAN BERBAGAI KONSENTRASI BIOSAKA DAN KONSENTRASI PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annuum L.) - Ramadhan, Revo Lianda; Eliyanti, Eliyanti; Swari, Elly Indra (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2026)
Red chili (Capsicum annuum L.) is a horticultural commodity with high economic value in Indonesia and is included in the group of national superior vegetables. This commodity is even one of the determinants of inflation rates in Indonesia. This study aims to examine the effect of interaction between Biosaka and NPK fertilizer and to obtain the concentration of Biosaka and NPK fertilizer concentration on the growth and yield of red chili (Capsicum annum L.). The research design used in this study was a Randomized Block Design (RAK), which consisted of two factors, namely the dose of Biosaka (P) and the concentration of NPK Fertilizer (16:16:16) (T). The first factor is Biosaka which consists of 4 levels, namely, p1: 0 ml·L-1 Biosaka, p2: giving 1 ml·L-1 Biosaka, p3: giving 2 ml·L-1 Biosaka, p4: giving 3 ml·L-1 Biosaka. The second factor is NPK fertilizer concentration which consists of 3 levels, namely, t1: 0 g·L-1 NPK (0%), t2: 1 g·L-1 NPK (50%), t3: 2 g·L-1 NPK (100%). The variables observed were plant height, dichotomous height, stem diameter, age at flowering, number of flowers per plant, age at fruiting, age at harvest, number of fruits per plant, fruit weight per plant, fruit length and fruit diameter. The results of the study showed that there was an interaction between various Biosaka applications and various NPK fertilizer applications on fruit diameter, but did not affect plant height, dichotomy height, stem diameter, flowering age, number of flowers per plant, fruiting age, harvest age, number of fruits per plant, fruit weight per plant, fruit length in red chili plants. The single application of Biosaka had a significant effect on dichotomy height and fruit diameter. The application of Biosaka concentration of 2 ml·L-1 showed the best growth and results because it provided the most optimal growth and result responses. The application of Biosaka 2 ml·L-1 on 100% NPK fertilizer showed the best growth and results in red chili plants for all observation variables.